2007
DOI: 10.1021/ja073798w
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Cross-β Core Structure of Amyloid Fibrils by Hydrogen−Deuterium Exchange Deep Ultraviolet Resonance Raman Spectroscopy

Abstract: Studying the structure of amyloid fibrils is important for the detailed understanding of fibrillogenesis at a molecular level. Amyloid fibrils are noncrystalline and insoluble, and thus are not amenable to conventional X-ray crystallography and solution NMR, the classical tools of structural biology. 1 Several specialized techniques with less general capabilities have been developed and utilized for probing fibrillar structure. Transmission electron microscopy (TEM) and scanning probe microscopy (SPM) provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
129
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

7
1

Authors

Journals

citations
Cited by 74 publications
(148 citation statements)
references
References 20 publications
(57 reference statements)
19
129
0
Order By: Relevance
“…The sensitivity of the amide M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 8 chromophore Raman signature to Ψ dihedral angle makes this technique uniquely capable of differentiating between globular and fibrillar β-sheet conformations and between parallel and antiparallel β-sheets [19,30]. The DUVRR spectrum of PFOs (Fig.…”
Section: Formation Of Acrylodan-labeledmentioning
confidence: 99%
“…The sensitivity of the amide M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 8 chromophore Raman signature to Ψ dihedral angle makes this technique uniquely capable of differentiating between globular and fibrillar β-sheet conformations and between parallel and antiparallel β-sheets [19,30]. The DUVRR spectrum of PFOs (Fig.…”
Section: Formation Of Acrylodan-labeledmentioning
confidence: 99%
“…Advanced statistical methods allow for retrieving of reliable information from data sets that is not otherwise evident. We have been successful in developing and applying advanced statistical analysis of Raman spectra for biochemical [19][20][21][22][23][24][25][26][27] and forensic purposes [7][8][9]11,13].…”
Section: Open Accessmentioning
confidence: 99%
“…Our studies have shown that amide I band of native lysozyme [77] is centered at 1660 cm −1 , whereas amide I bands of unordered lysozyme and lysozyme fibrillar β-sheet have maxima around 1667 cm −1 and 1674 cm −1 , respectively. [79] Accordingly, the high wavenumber shift of the amide I band indicates an increase in random coil or/and β-sheet contents of over the course of incubation. The noticeable sharpening of the amide I band at long incubation times is due to the formation of nucleus β-sheet structure.…”
Section: Duvrr Spectroscopic Characterization Of Lysozyme At Early Stmentioning
confidence: 99%